Global precipitation trends in 1900–2005 from a reconstruction and coupled model simulations. Issue 4 (26th February 2013) - Ren, Li; Arkin, Phillip; Smith, Thomas M.; Shen, Samuel S.P.
Abstract : [1] The trends of global precipitation in 1900–2005 are evaluated using a historical precipitation reconstruction and coupled model simulations, Coupled Model Intercomparison Project 5 (CMIP5) and Coupled Model Intercomparison Project Phase 3. A significant increasing trend in the global oceanic precipitation is identified in both the reconstruction and models. The trend from the reconstructed ocean precipitation is 0.04 mm day −1 over 100a (100 years) and is about twice that of the mean of all models. Over land, the spatial patterns of the trends from both the reconstruction and the models are similar to those shown in the Intergovernmental Panel on Climate Change Fourth Assessment Report. Over the ocean, both reconstruction and models show positive trends in the equatorial and subpolar regions and negative trends over the subtropics. However, the trend magnitude and the locations of the trend peaks are different near the equator (10°S to 10°N) between the reconstruction and the models. CMIP5 future simulations for the global mean project a continuing and stronger precipitation trend in the 21st century than the 20th century. Key Points: 20th century trends in the reconstruction. 20th century trends in CMIP5 and CMIP3 21st century trends in CMIP5